Variable vulnerability to climate change in New Zealand lizards - Scott Jarvie; Travis Ingram; David G. Chapple; Rodney A. Hitchmough; Stuart V. Nielsen; Joanne M. Monks (Journal of Biogeography, 2022)
Aim The primary drivers of species and population extirpations have been habitat loss, overexploitation and invasive species, but human‐mediated climate change is expected to be a major driver in future. To minimise biodiversity loss, conservation managers should identify species vulnerable to climate change and prioritise their protection. Here, we estimate climatic suitability for two species‐rich taxonomic groups, then use phylogenetic analyses to assess vulnerability to climate change. Location Aotearoa New Zealand (NZ). Taxa NZ lizards: diplodactylid geckos and eugongylinae skinks. Methods We built correlative species distribution models (SDMs) for NZ geckos and skinks to estimate climatic suitability under current climate and 2070 future climate scenarios. We then used Bayesian phylogenetic mixed models (BPMMs) to assess vulnerability for both groups with predictor variables for life‐history traits (body size and activity phase) and current distribution (elevation and latitude). We explored two scenarios: an unlimited dispersal scenario, where projections track climate, and a no‐dispersal scenario, where projections are restricted to areas currently identified as suitable. Results SDMs projected vulnerability to climate change for most modelled lizards. For species' ranges projected to decline in climatically suitable areas, average decreases were between 42% and 46% for geckos and 33% and 52% for skinks, although area did increase or remain stable for a minority of species. For the no‐dispersal scenario, the average decrease for geckos was 37%–52% and for skinks was 33%–52%. Our BPMMs showed phylogenetic signal in climate change vulnerability for both groups, with elevation increasing vulnerability for geckos, and body size reducing vulnerability for skinks. Main conclusions New Zealand lizards showed variable vulnerability to climate change, with most species' ranges predicted to decrease. For species whose suitable climatic space is projected to disappear from within their current range, managed relocation could be considered to establish populations in regions that will be suitable under future climates.